2015
DOI: 10.1155/2015/185891
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Impairment in Patients with Newly Diagnosed HIV Infection in Southwestern Nigeria

Abstract: Neurocognitive impairment is a detrimental complication of HIV infection. Here, we characterized the intellectual performance of patients with newly diagnosed HIV infection in southwestern Nigeria. We conducted a prospective study at Owo Federal Medical Center by using the adapted Wechsler Adult Intelligence Scale (WAIS). The raw scores were converted to standardized scores (z-scores) and correlated with clinical and laboratory findings. Fifty-eight HIV positive patients were recruited; 72% were in WHO stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…ART is thought to delay the onset of milder NCI 49 (common even in the era of HAART) 10 or to improve the performance of patients with an existing HIV-associated neurocognitive dysfunction. 50 Either way, being stable on ART may have resulted in comparable neurocognitive test performance between adults living with HIV and community controls in our sample and ART-naivety in the study by Sunmonu et al 32 may have explained why the authors observed strong significant group differences.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…ART is thought to delay the onset of milder NCI 49 (common even in the era of HAART) 10 or to improve the performance of patients with an existing HIV-associated neurocognitive dysfunction. 50 Either way, being stable on ART may have resulted in comparable neurocognitive test performance between adults living with HIV and community controls in our sample and ART-naivety in the study by Sunmonu et al 32 may have explained why the authors observed strong significant group differences.…”
Section: Discussionmentioning
confidence: 65%
“…Our findings generally contrast findings from other studies conducted in SSA. A Nigerian study by Sunmonu et al , 32 assessing intellectual performance of antiretroviral-naïve HIV-infected participants compared with a control group, found strong significant differences (p<0.01) with medium to large effect sizes (0.7–1.8). On the other hand, a study conducted in Uganda by Robertson et al 31 reported significant differences between HIV-infected subjects and controls for the backward digit span test (p<0.001) and tests of executive functioning (<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Since the average estimate of HIV-associated neurocognitive disorders was predisposed to considerable heterogeneity, we employed a subgroup analysis based on the country where the study was done, the assessment tool used to screen HIV-associated neurocognitive disorders, and the study design. The average estimate of HIV associated neurocognitive disorders in Europe ( 8 , 14 , 21 , 23 , 24 , 27 , 28 , 40 , 41 , 44 ) was found to be 50.015% (95% CI: 43.339, 56.691) whereas in Africa ( 10 , 13 , 18 , 20 , 25 , 30 , 31 , 35 , 37 39 , 45 50 ), Asia ( 17 , 26 , 34 , 36 , 43 ) and the United States of America (USA) ( 29 , 41 ) the average prevalence of HAND were 49.566% (95% CI: 41.342, 57.791) with ( I 2 = 96.6%, p < 0.001), 52.032 % (95% CI: 34.46, 69.604) with ( I 2 = 98%, p < 0.001) and 50.407% (95%CI: 45.555, 55.258) ( I 2 =100%, P < 0.001), respectively ( Figure 3 and Table 2 ). The average estimate of HIV associated neurocognitive disorders in studies which used International HIV Dementia Scale (IHDS) ( 8 , 10 , 12 14 , 17 , 20 , 25 , 35 37 , 39 , 43 , 44 , 46 , 48 50 , 66 ) was 36.883% (95%CI: 21.196, 52.571) and 59.956% (95%CI: 49.985, 69.928) at a cutoff points of IHDS <9.5 and IHDS <10, respectively ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated average of HAND in studies used the global dementia scale (GDS) ( 30 , 38 ) was 40.766% (95%CI: 31.995, 49.537). The estimated average of HAND in cross-sectional ( 8 , 10 , 12 14 , 17 20 , 23 , 25 , 26 , 28 , 30 , 31 , 34 – 40 , 45 50 ) cohort ( 8 , 21 , 23 , 24 , 27 , 29 , 41 , 43 , 44 ) and case-control ( 30 , 66 ) studies was 49.52% (95% CI: 43.490, 55.545) ( I 2 = 48.6%, P =1.00), 54.087% (95% CI: 45.087, 63.087) ( I 2 = 96%%, P < 0.001) and 44.45% (95% CI: 25.144, 63.756) ( I 2 = 94.8%, P < 0.001), respectively ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of forty studies (8, 10, 12-14, 16-49) that surveyed HIV associated neurocognitive disorders in 14107 HIV/AIDS patients were integrated in the current systematic review and meta-analysis study. Of the forty included studies; eleven were from Europe (8,14,20,22,23,26,27,39,40,43), twenty one were from Africa (10,13,17,19,24,29,30,34,(36)(37)(38)(44)(45)(46)(47)(48)(49), and six were from Asia (16,25,33,35,42) (fazel) and two from United States of America (USA) (28,40). Most of the included studies ( 28…”
Section: 2: Characteristics Of Included Studiesmentioning
confidence: 99%